Bank’s Digitalization and Financial Performance during Pandemic in Indonesia - Najwa Khairina (International Journal of Entrepreneurship, Business, and Creative Economy, 2022)
The pandemic-led recession has made a downturn in the banking industry’s performance. Digitalization is seen as a good strategy to support banks' business operations during the pandemic-led recession. This paper focus on how the banking and financial industry maintained their performance during the covid-19 led recessions through digitalization. I use descriptive statistics approach and regression analysis to analyze how digital transformation help to maintain business performance during a pandemic. In addition, I use regression analysis to estimate the effect of a pandemic on banks’ financial performance and how digital transactions may help to maintain banks’ performance. The regression estimation result shows that pandemic conditions associated with -0.177 points decrease in ROA while digital infrastructure may not have relations with banks’ ROA. Further, the volume of digital transactions is associated with the increase of bank's return on asset (ROA) as much as 10%. These results imply that even though pandemics have negative impacts on banks’ performance, empirical evidence shows that digital transactions have helped the banking industry to maintain its profit during the pandemic.